Experiencing Nokia : exploring the narratives of the former employees - Routa, Antonin (2020)
This case study focuses on narratives of former Nokia Corporation employees. The analysis aims to describe in what way former employees recall their employment with the once largest technological company in the world. The narratives were collected from various publicly available online sources such as blogs and social media posts. The targeted data were the first-person narratives. The analysis showed that there were key themes occurring among the collected narratives such as working experience, reasons for failure or layoff experience. The second stage of analysis implemented the theories of narratives attribution, which revealed the motivation behind the collected narratives. The identification of narrative attribution was based on the external and internal sources influencing the narration. The study provides the connection between past knowledge of Nokia Corporation, narrative and oral theories as well as cognition-emotion process of socio-psychological research. The discussion and conclusion part of the study offers discursive outlook on implication of narrative research in business and organizational studies. Moreover, the discussion debates the application and value of variety of other well established entrepreneurial study theories within the collected data set such as Tamara story. The theories from field of failed enterprises are applied as well. The narratives and its content offers practical insights into the working environment and overall perception of Nokia Corporation by former employees. In addition, the data set was determined as suitable base for further researches about Nokia Corporation. This research contributes to application of narratives within organizational studies as well as increasing the overall knowledge of Nokia Corporation. This study was conducted as part of large research project attempting to map the history of technology giants and reconstruct the reasons for their failures.